Coercion in mental health: a trial of the effectiveness of community treatment orders and an investigation of informal coercion in community mental health care - Tom Burns; Jorun Rugkåsa; Ksenija Yeeles; Jocelyn Catty (NIHR Journals Library, 2016)
Background: Coercion comprises formal coercion or compulsion [treatment under a section of the Mental Health Act (MHA)] and informal coercion (a range of treatment pressures, including leverage). Community compulsion was introduced in England and Wales as community treatment orders (CTOs) in 2008, despite equivocal evidence of effectiveness. Little is known about the nature and operation of informal coercion. Design: The programme comprised three studies, with associated substudies: Oxford Community Treatment Order Evaluation Trial (OCTET) - a study of CTOs comprising a randomised controlled trial comparing treatment on CTO to voluntary treatment via Section 17 Leave (leave of absence during treatment under section of the MHA), with 12-month follow-up, an economic evaluation, a qualitative study, an ethical analysis, the development of a new measure of capabilities and a detailed legal analysis of the trial design; OCTET Follow-up Study - a follow-up at 36 months; and Use of Leverage Tools to Improve Adherence in community Mental Health care (ULTIMA) - a study of informal coercion comprising a quantitative cross-sectional study of leverage, a qualitative study of patient and professional perceptions, and an ethical analysis. Participants: Participants in the OCTET Study were 336 patients with psychosis diagnoses, currently admitted involuntarily and considered for ongoing community treatment under supervision. Participants in the ULTIMA Study were 417 patients from Assertive Outreach Teams, Community Mental Health Teams and substance misuse services. Outcomes: The OCTET Trial primary outcome was psychiatric readmission. Other outcomes included measures of hospitalisation, a range of clinical and social measures, and a newly developed measure of capabilities - the Oxford Capabilities Questionnaire - Mental Health. For the follow-up study, the primary outcome was the level of disengagement during the 36 months. Results: Community treatment order use did not reduce the rate of readmission [(59 (36%) of 166 patients in the CTO group vs. 60 (36%) of 167 patients in the non-CTO group; adjusted relative risk 1.0 (95% CI 0.75 to 1.33)] or any other outcome. There were no differences for any subgroups. There was no evidence that it might be cost-effective. Qualitative work suggested that CTOs' (perceived) focus on medication adherence may influence how they are experienced. No general ethical justification was found for the use of a CTO regime. At 36-month follow-up, only 19 patients (6% of 329 patients) were no longer in regular contact with services. Longer duration of compulsion was associated with longer time to disengagement (p = 0.023) and fewer periods of discontinuity (p < 0.001). There was no difference in readmission outcomes over 36 months. Patients with longer CTO duration spent fewer nights in hospital. One-third (35%) of the ULTIMA sample reported lifetime experiences of leverage, lower than in the USA (51%), but patterns of leverage experience were similar. Reporting leverage made little difference to patients' perceived coercion. Patients' experiences of pressure were wide-ranging and pervasive, and perceived to come from family, friends and themselves, as well as professionals. Professionals were committed to patient-centred approaches, but felt obliged to assert authority when patients relapsed. We propose a five-step framework for determining the ethical status of offers by mental health professionals and give detailed guidance for professionals about how to exercise leverage. Conclusions: Community Treatment Orders do not deliver clinical or social functioning benefits for patients. In the absence of further trials, moves should be made to restrict or stop their use. Informal coercion is widespread and takes different forms. Trial registration: Current Controlled Trials ISRCTN73110773. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.